A Case Study of Outside Looking In (OLI): A Youth Development through Recreation Program for Aboriginal Peoples - Rovito, Alana (Université d'Ottawa / University of Ottawa, 2012)
Outside Looking In (OLI) is a youth development through recreation program for Aboriginal peoples in Canada. Through the analysis of semi-structured interviews, fieldnotes, and archival documents, in this thesis I examine OLI staff and Board members’ description of OLI’s creation and implementation processes. This thesis is written in the stand alone format and is comprised of two papers. The first paper shows that OLI staff and Board members describe OLI’s creation and implementation as relatively predetermined. At the same time, however, OLI incorporates collaborative approaches to various aspects of program design. While OLI facilitates collaborative processes that can contribute to Aboriginal self-determination, Eurocentric influences and broader colonial forces make efforts to achieve Aboriginal self-determination challenging. The second paper illustrates that OLI’s approach to Aboriginal youth development through recreation creates a hybrid third space that challenges colonial discourses. Together, this thesis not only describes the creation and implementation processes of a youth development through recreation program for Aboriginal peoples, but also how the tensions associated with Aboriginal self-determination and colonial relations of power can permeate such programs.
Keywords: Aboriginal Self-Determination; Colonialism; Youth Development; Recreation Programming; Hip-hop; Multimedia